The Sultan’s Legacy : How Young People in Yogyakarta Navigate Traditional Authority in an Era of Rational-Legal Authority - Naufalul Ihya Ulumuddin; Pusairi; Audea Septiana; Moh. Mudzakkir (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2025)
This study focuses on presenting how young people in Yogyakarta navigate traditional authority in their daily lives amid the dominance of rational legal authority. The research context was conducted in the context of understanding the phenomenon of a series of large-scale demonstrations in Indonesia from late August to early September 2025. This study uses a qualitative method with a case study approach. Data collection was conducted through direct interviews with five young people native to Yogyakarta who are pursuing higher education in Yogyakarta. The specific location that became the locus of this study was Yogyakarta for three main reasons. First, the unique socio-political conditions in Yogyakarta, which combine a democratic government system and a royal palace system. Second, the awareness of the youth of Yogyakarta as citizens of the province and citizens of the royal palace. Third, the actions of Sultan Hamengkubuwono X in controlling the masses when the demonstrations turned violent. The results of the study show that a leadership system based on traditional authority is not always negative. In fact, at certain moments, leadership based on traditional authority is more effective than leadership based on legal rational authority. This can be a further reflection on the model of modern community leadership, especially in Indonesia, regarding the appropriate leadership in overcoming social dynamics in community life